A holistic model of the role, development, and future of knowledge management: Proposal for exploratory research. (2nd November 2021) - Nakash, Maayan; Baruchson‐Arbib, Shifra; Bouhnik, Dan
Abstract: This paper presents our proposal for an exploratory research study. The objective of the research is to develop a conceptual framework of the interpretations, meanings, perceptions, and beliefs related to the role, development, and future of the knowledge management (KM) discipline. We propose to develop a holistic model that will depict professionals' perceptions of this issue: the combined perceptions of both KM consultants and knowledge managers. The proposed qualitative research will be based on three research tools: Semi‐structured in‐depth interviews, focus groups, and content analysis. The data will be analyzed using a thematic analysis method based on the grounded theory approach. We collected preliminary empirical evidence from international KM experts during 2020. The findings revealed a remarkable variety of issues that exist at the core of the KM discipline. These issues include the role and purpose of KM in knowledge‐intensive organizations, the implications of the existence or absence of KM, and views about future avenues for its development. Our intention is to explore these issues further by expanding the research to other KM professionals. Through this, we hope to assist in the positioning of the discipline in the age of knowledge. This research may contribute significantly to both the theoretical and practical aspects of KM. Its uniqueness is reflected in the voices of KM professionals. We foresee that our research will enable a better understanding of the evolution of KM as a discipline, its contemporary role, and its future possibilities.